2009
DOI: 10.1021/op9001092
|View full text |Cite
|
Sign up to set email alerts
|

Practical Diastereoselective Synthesis and Scale-up Study of (+)-2-((1R,2R,3R,5S)-2-Amino-6,6-dimethylbicyclo[3.1.1]hept-3-yl)ethanol: A Key Intermediate of the Novel Prostaglandin D2 Receptor Antagonist S-5751

Abstract: A new synthetic process was developed for (+)-2-((1R,2R,3R,5S)-2-amino-6,6-dimethylbicyclo[3.1.1]hept-3-yl)ethanol, a key intermediate of S-5751. Diastereoselective alkylation of (+)-nopinone with ethyl bromoacetate, formation of O-methyl oxime, and diastereoselective reduction with NaBH 4 -AlCl 3 could be safely carried out. Stereochemistry of the (1R,2R,3R,5S)-6,6-dimethylbicyclo[3.1.1]heptane ring was discussed to achieve high diastereoselectivity on these reactions. For the scale-up, detailed consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…In the Genzyme route, amide reduction was conducted using LiAlH 4 , which also worked well with amide 4 in our case (Table 4, entry 1). However, considering the safety issue related to LiAlH 4 for pilot-scale manufacturing, 15 alternative reagents were investigated (Table 4, entries 2−8). Early work showed that NaBH 4 /TFA gave low conversion in amide reduction (Table 4, entry 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the Genzyme route, amide reduction was conducted using LiAlH 4 , which also worked well with amide 4 in our case (Table 4, entry 1). However, considering the safety issue related to LiAlH 4 for pilot-scale manufacturing, 15 alternative reagents were investigated (Table 4, entries 2−8). Early work showed that NaBH 4 /TFA gave low conversion in amide reduction (Table 4, entry 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Nonetheless, NaBH 4 does not directly reduce the carboxylic acids by reason of its relatively weak reductive activity. To reduce carboxylic acid compounds effectively, many Lewis acids have been developed to improve the reduction activity of NaBH 4 including I 2 , 21 ZnCl 2 , 22 LiCl, 23 AlCl 3 , 24 CoCl 2 (ref. 25) and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Scheme summarizes the known methods for the reduction of esters with NaBH 4 in methanol. Addition of metal salts, such as LiCl, LiBr, MgCl 2 , CaCl 2 , ZnCl 2 , and AlCl 3 , to sodium borohydride increases its reduction capabilities (Scheme , entry 1). There are also reports of the reduction of esters using NaBH 4 in the presence of Ce or Co catalyst (Scheme , entry 2) supported on cationic surfaces . Under reflux conditions, NaBH 4 has been reported to reduce esters in protic solvents (Scheme , entry 3). , Esters bearing substituents like hydroxyl/oxo/amino in the α- or β-positions have been reduced by NaBH 4 via intramolecular hydride transfer (Scheme , entry 4). Unfortunately, alcohol solvents, such as methanol, are not compatible with NaBH 4 at elevated temperatures because decomposition of NaBH 4 becomes competitive with the reduction.…”
Section: Introductionmentioning
confidence: 99%